Fear‐related barriers to physical activity among adults with overweight and obesity: A narrative synthesis scoping review. (25th June 2021) - Hamer, Oliver; Larkin, Derek; Relph, Nicola; Dey, Paola
Summary: Physical activity is a health behavior contributing to successful weight management. Adults with overweight and obesity find it challenging to meet recommended activity guidelines because of a range of barriers, some of which are not yet fully understood. A barrier receiving limited consideration, compared with other literature within this field, is that of fear. The purpose of this scoping review was to establish the extent of literature on fear‐related barriers to physical activity in adults with overweight or obesity and to identify gaps in this literature. The review followed the scoping review framework outlined by Arksey and O'Malley and adhered to the Preferred Reporting Items for Systematic reviews and Meta‐Analyses extension for Scoping Reviews guidelines. The findings of the identified papers were charted thematically using a framework of fears and age group. In total, 34 studies were included that identified nine different fears related to barriers to activity in this population. However, only a small number of studies ( n  = 5) had explicitly intended to explore fear‐related barriers. There were notable knowledge gaps including activity‐related fear of pain and movement in adults under 45 years of age. There is a strong rationale to further explore these fears because they may restrict health promoting behavior.